(untitled) (African Journal of Biomedical Research, 2024)
The burden of hypertension is becoming worrisome in a resource-constrained continent like Africa. There is a dearth of information on the extent of the present use of interprofessional care in the continent, its effectiveness and factors that could limit its use. This systematic review sought to describe the extent as well as the effectiveness of the use of interprofessional care in the management of hypertension across the African regions. A comprehensive literature search was conducted on Pubmed, Google Scholar and ScienceDirect. The search covered the period from 1993 to 2023 (30 years period). This review was done in line with the guidelines set out by Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. A total of 35 articles were included in the review out of which the East African region had 10 (29%), Central African 3 (9%), North African 4 (11%), Southern African 7 (20%) and West Africa 11 (31%). The assessment of team cooperation, institutional or government support, right operational environment, free inter-professional communication, cost-effectiveness in patient management and easy access to care for the patients in the articles was generally affirmative to indicate effectiveness of interprofessional care. A few cases of interprofessional conflicts were also reported. Interprofessional care of hypertension is proven to be beneficial and effective in the management of hypertension in Africa but grossly under-reported. Its use may be threatened by lack of team cooperation, occurrence of conflicts between the health workers and inadequate support from government among other factors.